2009
DOI: 10.1080/10824660802427652
|View full text |Cite
|
Sign up to set email alerts
|

Halting the Summer Achievement Slide: A Randomized Field Trial of the KindergARTen Summer Camp

Abstract: In this randomized field trial of KindergARTen Camp, a 6-week summer enrichment program in literacy and the fine arts, we analyzed the summer learning outcomes of 93 treatment and 35 control students from high-poverty schools in Baltimore, Maryland. This experiment offers evidence concerning the causal effect of the program on 5 measures of students' literacy achievement. We found treatment effects during the summer months that were of both practical and statistical significance on the Developmental Reading As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 14 publications
1
30
0
2
Order By: Relevance
“…For example, Borman, Goetz, and Dowling (2009) found positive and significant effects of the KindergARTen 6-week literature and fine arts summer camp on literacy development. The program drew students from over 100 highpoverty schools in Baltimore.…”
Section: Summer Time-use Gapsmentioning
confidence: 94%
“…For example, Borman, Goetz, and Dowling (2009) found positive and significant effects of the KindergARTen 6-week literature and fine arts summer camp on literacy development. The program drew students from over 100 highpoverty schools in Baltimore.…”
Section: Summer Time-use Gapsmentioning
confidence: 94%
“…One 78 was excluded from analysis because of limited quality of execution. Of the remaining 25 studies, 6 (reported in 5 publications) were of good quality of execution 56,70,75,76,79 and 19 were of fair quality. 55,57–69,7174,77 The combined analysis included 57 studies.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…également aux élèves des écoles de langue française en Ontario et si les programmes d'apprentissage pendant l'été peuvent améliorer le rendement scolaire. Un ensemble d'études américaines a démontré qu'en effectuant quotidiennement des heures de lecture additionnelles, les jeunes lecteurs des programmes d'apprentissage pendant l'été peuvent compenser le retard cumulé pendant l'été (Borman et Dowling 2006;Borman, Goetz et Dowling 2009). Bien que certaines évaluations rapportent des résultats mitigés, il n'en demeure pas moins qu'en général, les études indiquent que les interventions pendant les vacances aident les enfants issus de milieux défavorisés à éviter des pertes de compétences, à acquérir de nouvelles aptitudes, et à réduire les écarts de performance (Cooper 2004).…”
unclassified
“…Bien que certaines évaluations rapportent des résultats mitigés, il n'en demeure pas moins qu'en général, les études indiquent que les interventions pendant les vacances aident les enfants issus de milieux défavorisés à éviter des pertes de compétences, à acquérir de nouvelles aptitudes, et à réduire les écarts de performance (Cooper 2004). Inspirées par la recherche sur l'apprentissage estival, plusieurs villes américaines ont implanté une variété de programmes d'été avec succès (Borman et Dowling 2006;Borman, Goetz et Dowling 2009;Roderick, Jacob et Bryk 2004).…”
unclassified